2021
DOI: 10.1007/s12311-021-01342-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional Gradients of the Cerebellum: a Review of Practical Applications

Abstract: The Version of Record is the version of the article after copy-editing and typesetting, and connected to open research data, open protocols, and open code where available. Any supplementary information can be found on the journal website, connected to the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The diffusion embedding method has proven useful for revealing the topographical pattern by recovering a low-dimensional spatial representation (functional gradients) from high-dimensional functional connectivity data 27,33,34,48 . Based on the diffusion embedding, our results and previous studies 25,26 revealed a similar functional gradient for the intra-cerebellar and the cerebello-cerebral functional connectivity of the human brain. The observation in humans suggested that the cerebello-cerebral connections may influence the intrinsic functional connectivity of cerebellar regions, which contributed to similar spatial distribution between the two types of gradients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The diffusion embedding method has proven useful for revealing the topographical pattern by recovering a low-dimensional spatial representation (functional gradients) from high-dimensional functional connectivity data 27,33,34,48 . Based on the diffusion embedding, our results and previous studies 25,26 revealed a similar functional gradient for the intra-cerebellar and the cerebello-cerebral functional connectivity of the human brain. The observation in humans suggested that the cerebello-cerebral connections may influence the intrinsic functional connectivity of cerebellar regions, which contributed to similar spatial distribution between the two types of gradients.…”
Section: Discussionsupporting
confidence: 82%
“…The software Mrtrix3 was used for all diffusion tracking 26 . Following its standard pipeline, the dwi2response was used to estimate the response function of the preprocessed dMRI data by the dhollander method.…”
Section: Structural-connectivity-based Mapping and Functional Connect...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, an increasing number of publicly accessible large studies (e.g., ABCD) and consortium-driven data repositories (e.g., ENIGMA) are poised to generate exactly such maps. A more comprehensive mapping to behavior will likely also require the systematic integration of the macroscale hierarchical gradient with subcortical structures (e.g., amygdala, ventral striatum, hippocampus, thalamus, basal ganglia) critical for experience-dependent learning and cerebellar networks critical for feed-forward monitoring of both actions and thoughts (Guell, 2021; Tian et al, 2020).…”
Section: Macroscale Brain Organization and Self-regulatory Dysfunctio...mentioning
confidence: 99%
“…Building upon our work, we envision that further exploration of the cerebellar output circuitry will generate valuable contributions to the field of translational and precision psychiatry. Novel gradient-based analysis strategies ( 49 ) can be used to complement existing brain mapping approaches ( 50 ), and to detect functional abnormalities in psychiatric disorders that may remain hidden using other methods of analysis ( 51 , 52 ). Cerebellum's interplay with cerebral cortical dynamics is still poorly understood.…”
Section: Future Directionsmentioning
confidence: 99%